2019
DOI: 10.1111/jdv.15708
|View full text |Cite
|
Sign up to set email alerts
|

Association between smoking and Behçet's disease: a nationwide population‐based study in Korea

Abstract: Background There have been conflicting results about the association between Behçet's disease and smoking. Smoking has been reported to be a protective factor for Behçet's disease, whereas smoking may have a role in triggering Behçet's disease. Objectives The aim of this study was to investigate the incidence of Behçet's disease in Korea according to smoking status using nationwide population data. Methods We analysed clinical data from individuals 20 years of age and older who received a health examination ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 65 publications
(125 reference statements)
0
15
0
Order By: Relevance
“…A study from Japan has shown that neurological involvement is more likely to develop in male smokers [39], suggesting that the recent shrinkage in cluster 5 is relate to fewer male smokers in Japan, though positive or negative effects of smoking on BD have been controversial [39][40][41][42]. Alternatively, improvement of oral hygiene [43] and altered microbiota [44] can also contribute to lowering the rate of serious BD phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Japan has shown that neurological involvement is more likely to develop in male smokers [39], suggesting that the recent shrinkage in cluster 5 is relate to fewer male smokers in Japan, though positive or negative effects of smoking on BD have been controversial [39][40][41][42]. Alternatively, improvement of oral hygiene [43] and altered microbiota [44] can also contribute to lowering the rate of serious BD phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Development of aphthous ulcers is associated with cessation of smoking [44][45][46][47][48][49][50] . The beneficial effects of smoking on oral ulcers in Behçet's disease has been shown in several reports [34][35][36] . Behçet's disease oral lesions appear after cessation of smoking; therefore, the beneficial effects of nicotine have been suggested [51][52][53][54] .…”
Section: Discussionmentioning
confidence: 92%
“…Smoking is known to have detrimental effects on and a positive association with psoriasis [16][17][18][19] , palmoplantar pustulosis, 20 and hidradenitis suppurativa [21][22][23][24][25][26][27] . However, several autoimmune skin diseases, such as pemphigus vulgaris, foliaceous, and 28-33 Behçet's disease [34][35][36] , show a negative association with smoking. We recently reported that the incidence of Behçet's disease in current smokers was significantly decreased compared to that of never-smokers in South Korea 36 .…”
mentioning
confidence: 99%
“…It has been suggested that smoking increases the risk of relapse of inflammatory and autoimmune diseases, in general [84][85][86]. Lee et al [87] reported that smoking and Behçet disease were closely associated in a Korean population-based study. Costa et al [88] also reported that smoking was associated with the risk of uveitis in Portuguese patients with spondyloarthropathies.…”
Section: Discussionmentioning
confidence: 99%